2019
DOI: 10.1111/echo.14397
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of mitral valve area in patients with mitral stenosis by 3D echocardiography: A comparison between direct planimetry on 3D zoom and 3D quantification

Abstract: Background Measurement of the mitral valve area (MVA) in patients with mitral stenosis (MS) by 3D echocardiography (3DE) is usually done via 3D quantification (3DQ). The present study on patients with severe MS sought to evaluate the agreement regarding the MVA measurement between 3DQ and direct planimetry on 3D zoom and also between 3DE and 2DE. Methods Twenty‐six patients (22 female, mean age:34.5 ± 14.0 years) with severe MS diagnosed by 2D transthoracic echocardiography(2DTTE) underwent 3D transesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Eibel et al [13] demonstrated that the direct delineation in the en-face 3D-TEE mode leads to a non-significant underestimation of MVA compared to MPR measurements in a cohort of patients who predominately had a normal MVA. Sadeghian et al [18] found that MVA MPR overestimated the MVA compared to MVA obtained by direct planimetry on the 3D zoom mode in rheumatic MS patients, which is in agreement with our study. The mean difference found in their study was approximately 0.9 cm 2 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Eibel et al [13] demonstrated that the direct delineation in the en-face 3D-TEE mode leads to a non-significant underestimation of MVA compared to MPR measurements in a cohort of patients who predominately had a normal MVA. Sadeghian et al [18] found that MVA MPR overestimated the MVA compared to MVA obtained by direct planimetry on the 3D zoom mode in rheumatic MS patients, which is in agreement with our study. The mean difference found in their study was approximately 0.9 cm 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, 3D direct planimetry has more frequently been used in clinical practice as a fast way to measure the MVA [15][16][17]. However, research assessing the effectiveness of the 3D direct planimetry method and its comparison to the MPR method is lacking [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this method, planimetry was applied at en face MV orientation from both left atrial and left ventricular sides. Planimetry at both 3D-direct and 3D-MPR methods was performed on MV lea ets tips in mid diastole during the maximal opening, at the smallest ori ce dimension (11,12,13). All measurements were done with an expert echocardiographist and were subsequently reviewed by a second echocardiographist.…”
Section: D -Teementioning
confidence: 99%
“…We compared the results of these two methods at the valve area below 1 cm 2 , 1-1.5 cm 2 and above 1.5 cm 2 in large numbers of patients with MS to assess the role of mitral valve shape on planimetry. Moreover, we evaluated the association between 2D-TTE and 3D-TEE planimetry results, with a consideration of their moderate to good agreement which is addressed at some previously published studies (13).…”
Section: Introductionmentioning
confidence: 99%
“…Mitral valve area (MVA) is technically measured by two-dimensional (2D) planimetry with high precision to assess the severity of mitral pathological changes, such as stenosis (1). However, the improvement of imaging methods using three-dimensional techniques has been considered in some studies to achieve the accurate values of these changes and minimize diagnostic errors (especially in the presence of distorted valvular tip or poor echo widow) (2).…”
Section: Introductionmentioning
confidence: 99%